2022
DOI: 10.3389/fcell.2022.886153
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Organoids for Regenerative Medicine and Cancer Research

Abstract: In recent years, the development of ex vivo organoid cultures has gained substantial attention as a model to study regenerative medicine and diseases in several tissues. Diabetes and pancreatic ductal adenocarcinoma (PDAC) are the two major devastating diseases affecting the pancreas. Suitable models for regenerative medicine in diabetes and to accurately study PDAC biology and treatment response are essential in the pancreatic field. Pancreatic organoids can be generated from healthy pancreas or pancreatic tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 120 publications
0
5
0
Order By: Relevance
“…Ackr3 + and Flrt3 + cells (medium-big duct-derived clusters) and CD166/Alcam + cells (pan-ductal). CD133/Prominin, was selected as stem cell marker already used to test ductal cell stemness (reviewed 52 ). Glut1/Slc2a1 was used to isolate a fraction of ductal cells, although it does not define a cluster.…”
Section: Resultsmentioning
confidence: 99%
“…Ackr3 + and Flrt3 + cells (medium-big duct-derived clusters) and CD166/Alcam + cells (pan-ductal). CD133/Prominin, was selected as stem cell marker already used to test ductal cell stemness (reviewed 52 ). Glut1/Slc2a1 was used to isolate a fraction of ductal cells, although it does not define a cluster.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be mentioned that cells in organoid culture are, in fact, more ductal and progenitor-like than acinar cells found within the intact pancreas, given that organoid culture selects for progenitor cells, and organoids are grown in the presence of stem cell factors. Both acinar and ductal cells can initiate organoid formation; however, only the ductal-like cells are capable of growth in organoid culture over extended passages ( 51 ).…”
Section: Resultsmentioning
confidence: 99%
“… 171 The establishment of pancreatic ductal adenocarcinoma organoids is typically achieved by collecting tumor tissues from patients ( Figure 10(b) ), which are then used for drug screening to predict patient response to chemotherapy and elucidate the associated mechanisms ( Figure 10(a and c )). 172 174 For instance, Tsai et al 63 cultured organoids from the tumor tissues of 28 patients with pancreatic cancer, and performed immunohistochemical and immunofluorescent evaluation to characterize organoid expression of tumor markers Maspin, Muc5ac, and CRR9, pancreatic marker PDX1, and gastroenteropancreatic and hepatobiliary epithelial marker CK19 ( Figure 10(d) ). They found that pancreatic cancer tumor organoids have similar histological features at primary tumors.…”
Section: Classification Of Digestive Tract Tumor Organoidsmentioning
confidence: 99%
“…(a) Pancreatic cancer organoids used to study the role of PDAC driver mutations. Adapted from Casamitjana et al 172 (b) Schematic of human pancreatic ductal organoid (hPDO) establishment. Adapted from Below et al 174 (c) PDOs, a model to predict the patient response to chemotherapy and define new treatment-induced vulnerability.…”
Section: Classification Of Digestive Tract Tumor Organoidsmentioning
confidence: 99%